DEVELOPMENT AND TESTING OF A CAPACITIVE DIGITAL SOIL MOISTURE SENSOR WITH PRINTED CIRCUIT BOARD AS A PROBE (Nigerian Journal of Technology, 2020)
The quantity and quality of water present in the soil determine to a greater extent the performance of agricultural crops. Real-time determination of moisture content has a greater advantage over the traditional gravimetric method of determining soil moisture content. Thus, this work was based on the design and construction of a cost effective digital capacitive soil moisture sensor for real-time measurement. The moisture sensors comprised four integrated units namely: power supply unit with a 9V DC battery as a power source, sensor unit with a locally sourced Printed Circuit Board (PCB) as the single sensing probe, control unit made up of PIC16f877 microcontroller programmed with a C language and the C source code compiled in Corporate Computer Services Compiler (CSS C) compiler development environment, and a 16x2 display unit which displays the readings in percentage moisture content (%MC) and capacitance (µF) of the soil obtained from the sensor on its screen. Standard gravimetric moisture content was carried out to get the calibration factor which was used to calibrate the sensor for reliability. The validation was done by taking the reprogrammed (calibrated) sensor to the field for further measurement, after which soil samples were collected for further gravimetric analysis. A regression equation was obtained by plotting the moisture content obtained from gravimetric method (%MCG) against that from sensor reading (%MCS) with a high degree correlation coefficient (R2) of 0.998. The developed capacitive soil moisture sensor is cheap, portable, reliable and easy to use even by local farmers. http://dx.doi.org/10.4314/njt.v39i3.32